Ligand-modified Pd / C catalyst, preparation thereof and application of ligand-modified Pd / C catalyst in selective hydrogenation reaction of nitrogen-containing alkyne
The ligand-modified Pd/C catalyst was prepared by impregnation coordination method, and organic ligands such as porous carbon support and oxalanilide were coordinated with palladium nanoparticles, which solved the problem of catalyst poisoning and inactivation in the selective hydrogenation reaction of nitrogen-containing alkynes, and achieved a catalytic effect with high selectivity and anti-toxicity performance.
Patent Information
- Application Number
- CN202411719024.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-11-28
AI Technical Summary
It is difficult to develop a catalyst that can exhibit high selectivity and anti-toxicity properties in selective hydrogenation reactions of nitrogen-containing alkynes, especially due to strong coordination between nitrogen atoms and metal atoms, resulting in catalyst poisoning and inactivation.
The ligand modified Pd/C catalyst was prepared by a simple impregnation coordination method, and organic ligands such as porous carbon support and oxalanilide were coordinated with palladium nanoparticles to form a stable catalyst to ensure that the palladium nanoparticles remain stable and dispersible in high temperature and reaction liquid.
Highly efficient catalysis in selective hydrogenation reaction of nitrogen-containing alkynes, with product selectivity up to 97%, and excellent anti-sulfur poisoning ability. The catalyst has good stability under air, solvent or high temperature conditions and can be reused.
Smart Images

Figure CN119771499A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a ligand-modified Pd / C catalyst, its preparation and application in the selective hydrogenation reaction of nitrogen-containing alkynes. Background Art
[0002] The selective hydrogenation of alkynes is an important step in industrial production. Its semi-hydrogenated products, olefins, are widely used in the synthesis of fine chemicals, pesticides and pharmaceutical intermediates. However, due to the high adsorption energy of olefins on the continuous palladium surface, it is not conducive to their rapid desorption, resulting in undesirable overhydrogenation products. Therefore, maintaining high selectivity of the target product is the key to industrial production.
[0003] Nitrogen is one of the most abundant elements on earth, and nitrogen-containing compounds are ubiquitous in nature, among which nitrogen-containing alkynes / olefins are involved in many fields such as the chemical and pharmaceutical fields and the life science fields. Nitrogen-containing olefins are usually obtained by semi-hydrogenation of the corresponding alkynes, but a thorny industrial problem is that nitrogen atoms have lone pairs of electrons and can act as Lewis bases to strongly coordinate with metal atoms (especially noble metals), isolating active sites and preventing reactant molecules from approaching the active center, resulting in catalyst poisoning and deactivation. So far, the selective hydrogenation of nitrogen-containing alkynes has rarely been reported because the poisoning of noble metal ions by heteroatoms has limited reactions. Therefore, it is urgent to develop a catalyst with both selectivity and anti-toxicity for the semi-hydrogenation of nitrogen-containing alkynes.
[0004] In heterogeneous catalysis, the traditional anti-poisoning strategy is to encapsulate metal nanoparticles in a structural shell, use metal heteroatoms (N / P / S, etc.) as catalysts, or dope metals with foreign atoms. Frank's research group synthesized a new heterogeneous Ru-S catalyst that can reduce unstable groups such as aromatics, halides, and olefins under mild conditions. More specifically, it shows a wide range of tolerance to various poisoned (sulfides, disulfides, thiophenes, and sulfoxides) and medically relevant (sulfonamides and sulfonyl chlorides) sulfur-containing functional groups (J.Am.Chem.Soc.2024,146,5864-5871). Zhang et al. used P-rich and C-rich polymers as precursors to encapsulate metal phosphide nanoparticles in a two-dimensional defect-rich graphitic carbon shell, and adjusted the carbon layer thickness by changing the molar ratio of metal to phosphorus. The prepared catalyst has excellent selectivity in the semi-hydrogenation reaction of phenylacetylene and exhibits high resistance to sulfur poisoning, among which the selective permeation of the carbon shell is the key to enhancing the stability of the catalyst (Chemical Engineering Journal 463 (2023) 142505). Although these methods effectively improve the anti-poisoning ability of the catalyst, there are still a series of disadvantages, such as high metal loading, leaching of active species in the solution, and inaccessibility of active sites.
[0005] There is an urgent need to develop a highly efficient anti-poisoning catalyst with a simple preparation method, low metal loading and low cost. Due to the unique property that organic ligands have good coordination ability with metal ions and can further anchor them on the carrier, the present invention adopts a simple impregnation coordination method to prepare a highly efficient Pd / C catalyst with anti-poisoning performance. Summary of the invention
[0006] In view of the above technical problems existing in the prior art, the purpose of the present invention is to provide a ligand-modified Pd / C catalyst and its preparation and application in the selective hydrogenation reaction of nitrogen-containing alkynes. The Pd / C catalyst is synthesized by a simple impregnation coordination method. The Pd / C catalyst has good stability in air, solvent or high temperature conditions and can be reused under the same reaction conditions. It is applied to the selective hydrogenation reaction of nitrogen-containing alkynes and exhibits excellent catalytic performance and resistance to sulfur poisoning.
[0007] The technical solution adopted by the present invention is as follows:
[0008] A ligand-modified Pd / C catalyst comprises a porous carbon carrier, palladium nanoparticles loaded on the carrier and an organic ligand coordinated on the catalyst surface, wherein the mass of the palladium nanoparticles is 0.5-2% of the mass of the porous carbon carrier, the organic ligand is selected from at least one of oxalic acid anilide, L-lysine, ethylenediaminetetraacetic acid or oleylamine, and the molar ratio of the organic ligand to palladium is 1-8:1.
[0009] Furthermore, the mass of the palladium nanoparticles is 0.8-1.2% of the mass of the porous carbon support, the organic ligand is selected from oxalic acid anilide, and the molar ratio of the organic ligand to palladium is 2-3:1.
[0010] Furthermore, the preparation method of the porous carbon carrier includes the following steps: cellulose and ammonium bicarbonate are evenly mixed in a mortar at a mass ratio of 1:0.8-1.2, then calcined at 700-900°C for 1-3h under Ar atmosphere, cooled to room temperature, and the obtained black powder is washed and dried overnight to obtain the porous carbon.
[0011] The preparation method of a ligand-modified Pd / C catalyst comprises the following steps: adding an organic ligand to anhydrous ethanol, stirring evenly, then adding a palladium precursor solution, stirring at room temperature overnight, then adding a porous carbon carrier, wherein the concentration of the porous carbon carrier dispersed in the anhydrous ethanol is 5-30 g / L, transferring the mixed solution to a 70-90°C oil bath heating environment and continuing to stir until the ethanol is completely evaporated, and reducing the obtained black powder at 180-250°C for 1-3 hours in a hydrogen atmosphere to obtain the catalyst.
[0012] Furthermore, the palladium precursor is Pd(NO 3 ) 2 , PdCl 2 or K2 PdCl 4 , preferably Pd(NO 3 ) 2 The mass of the Pd element in the palladium precursor is 0.5-2% of the mass of the porous carbon support, preferably 0.8-1.2%.
[0013] Furthermore, in the preparation method of a ligand-modified Pd / C catalyst, the organic ligand is selected from at least one of oxalic acid anilide, L-lysine, ethylenediaminetetraacetic acid or oleylamine, preferably oxalic acid anilide, and the molar ratio of the organic ligand to palladium is 1-8:1, preferably 2-3:1.
[0014] The present invention also provides a ligand-modified Pd / C catalyst, its preparation and application in the selective hydrogenation reaction of nitrogen-containing alkynes. The nitrogen-containing alkynes are mixed with a solvent, and then the reaction liquid is selectively hydrogenated under the action of the Pd / C catalyst in a hydrogen atmosphere to generate nitrogen-containing olefins; wherein the temperature of the hydrogenation reaction is 0-100°C, and the hydrogen pressure of the reaction is 0.1-4MPa; and the solvent is water, ethanol, dichloromethane, tetrahydrofuran or n-hexane.
[0015] Furthermore, the mass of the catalyst is 1-10%, preferably 2-5%, of the mass of the nitrogen-containing alkyne; the temperature for the selective hydrogenation reaction is 25-40° C.; the hydrogen pressure of the reaction is 0.1-0.5 MPa; and the solvent is ethanol.
[0016] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:
[0017] 1. The present invention adds oxalylanilide, loads it on porous carbon after simple impregnation coordination, and obtains palladium nanoparticles coordinated with oxalylanilide after hydrogen reduction. The preparation method of the catalyst is simple, time-consuming, low in production cost and has a low metal loading.
[0018] 2. Since the palladium nanoparticles are anchored on the carrier by organic ligands, their sintering and agglomeration in a high-temperature reducing atmosphere and their leaching in the reaction solution are greatly suppressed, so the catalyst palladium nanoparticles prepared by the present invention have uniform particle size and good dispersibility. The Pd / C catalyst has good stability in air, solvent or high temperature conditions and can be reused under the same reaction conditions.
[0019] 3. The ligand-modified Pd / C catalyst of the present invention and its application in the selective hydrogenation reaction of nitrogen-containing alkynes are universal, not only applicable to homemade Pd / C, but also applicable to commercial Pd / C, and have good industrial prospects. The introduction of oxalylanilide can change the electronic structure of palladium, increase the electron density of palladium species, and thus promote H 2The activation and dissociation of the catalyst are optimized by constructing metal-ligand electronic interactions, promoting the desorption of nitrogen-containing olefins and weakening the enrichment of nitrogen species on the palladium surface, thereby improving the catalytic activity, selectivity and anti-poisoning performance of the selective hydrogenation of nitrogen-containing alkynes. When the Pd / C catalyst of the present invention is used to selectively hydrogenate nitrogen-containing alkynes to prepare nitrogen-containing olefins, the reactant conversion rate is 99%, the product selectivity is as high as 97%, and there is no obvious over-hydrogenation even if the reaction time is extended. At the same time, a certain amount of thiophene is added to the reaction system, and the ligand-modified catalyst still maintains a high activity, reflecting its more excellent anti-sulfur poisoning ability. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is a transmission electron microscope image of the catalyst prepared in Example 1;
[0021] Figure 2 This is a high-resolution transmission electron microscopy image of the catalyst prepared in Example 1; DETAILED DESCRIPTION
[0022] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0023] The particle size of the cellulose used in the preparation of the porous carbon carrier in the embodiment of the present invention is 65 μm, and it is purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0024] In the embodiment of the present invention, the preparation steps of the homemade porous carbon carrier are as follows: cellulose and ammonium bicarbonate are mixed evenly in a mortar at a mass ratio of 1:1, then calcined at 800°C for 2h under an Ar atmosphere, and cooled to room temperature. The obtained black powder is washed with water overnight and dried to obtain the porous carbon carrier powder.
[0025] Example 1 Self-made Pd / C catalyst modified with oxalylanilide ligand (molar ratio 1:2)
[0026] 9 mg of oxalylanilide (0.0375 mmol) was placed in a 20 ml glass bottle, 12 ml of anhydrous ethanol was added, stirred evenly, and 1 ml of Pd(NO 3 ) 2 The solution (Pd mass concentration is 2 mg / ml) was stirred at room temperature overnight, and then 200 mg of self-made porous carbon support powder was added, and the mixture was transferred to an 80°C oil bath and continued to be stirred until the ethanol was completely evaporated. The obtained black powder was reduced at 200°C for 2h under a hydrogen atmosphere to obtain the catalyst.
[0027] The catalyst prepared in Example 1 was characterized by transmission electron microscopy (TEM) and high resolution transmission electron microscopy (HRTEM). Figure 1 and Figure 2As shown. Figure 1 It can be seen that the palladium nanoparticles were successfully loaded onto the porous carbon, and the particle size was relatively uniform and the dispersion was good. The average particle size was calculated by counting more than 200 nanoparticles and was 5.0nm. Figure 2 Specific and clear palladium lattice fringes can be seen with a lattice spacing of 0.229 nm, which is attributed to the Pd(111) plane.
[0028] The catalyst prepared in Example 1 was characterized by inductively coupled plasma mass spectrometry and then analyzed by EDS spectrum. The results showed that the Pd content in the catalyst of Example 1 was 0.9%.
[0029] Example 2 Commercial Pd / C catalyst modified with oxalylanilide ligand
[0030] 43 mg of oxalic acid anilide was placed in a 50 ml glass bottle, 20-30 ml of anhydrous ethanol was added, and after stirring evenly, 500 mg of commercial Pd / C catalyst (the Pd loading on the catalyst carrier was 10%, and the water content of the catalyst was 55%) was added, and stirred at 60° C. for 1 h, and then the temperature was increased and stirring was continued until the ethanol was completely evaporated. The obtained black powder was reduced at 200° C. for 2 h in a hydrogen atmosphere to obtain the catalyst.
[0031] Example 3 Homemade Pd / C catalyst based on oxalylanilide ligand (molar ratio 1:1)
[0032] The steps for preparing the catalyst of Example 3 were repeated as in Example 1, with the only difference being that "the amount of oxalylanilide added was replaced with 4.5 mg", and the other conditions remained unchanged, to finally obtain the catalyst.
[0033] Example 4 Homemade Pd / C catalyst based on oxalylanilide ligand (molar ratio 1:4)
[0034] The steps for preparing the catalyst of Example 4 were repeated in Example 1, with the only difference being that "the amount of oxalylanilide added was replaced with 18 mg" and the other conditions remained unchanged, and finally the catalyst was obtained.
[0035] Example 5 Homemade Pd / C catalyst based on oxalylanilide ligand (molar ratio 1:8)
[0036] The preparation steps of the catalyst in Example 5 were repeated in Example 1, with the only difference being that "the amount of oxalylanilide added was replaced with 36 mg" and the other conditions remained unchanged, and finally the catalyst was obtained.
[0037] Example 6 Self-made Pd / C catalyst modified with L-lysine ligand (molar ratio 1:2)
[0038] The steps for preparing the catalyst of Example 5 were repeated in Example 1, except that "0.0375 mmol of oxalylanilide was replaced by an equal molar amount of L-lysine", and the other conditions remained unchanged, and the catalyst was finally obtained.
[0039] Example 7 Self-made Pd / C catalyst modified with ethylenediaminetetraacetic acid ligand (molar ratio 1:2)
[0040] The preparation steps of the catalyst in Example 7 were repeated in Example 1, with the only difference being that "0.0375 mmol of oxalylanilide was replaced by an equal molar amount of ethylenediaminetetraacetic acid", and the other conditions remained unchanged, to finally obtain the catalyst.
[0041] Example 8 Self-made Pd / C catalyst modified with oleylamine ligand (molar ratio 1:2)
[0042] The preparation steps of the catalyst in Example 8 were repeated in Example 1, with the only difference being that "0.0375 mmol of oxalylanilide was replaced by an equal molar amount of oleylamine", and the other conditions remained unchanged, and the catalyst was finally obtained.
[0043] Example 9: Semi-hydrogenation of 3-acetylenequinoline using Pd / C catalyst
[0044] 306 mg of 3-acetylenequinoline, 10 mg of catalyst and 5 mL of ethanol were added to a 50 mL stainless steel autoclave, and the stainless steel autoclave was filled and exhausted with hydrogen for 3 times (i.e., the air in the stainless steel autoclave was replaced by hydrogen and the air in the stainless steel autoclave was emptied), and then filled with hydrogen to 0.1 MPa and sealed, and heated in a 30°C water bath with magnetic stirring to carry out selective hydrogenation reaction for a period of time. Sampling analysis was carried out, and the reaction liquid was detected by gas chromatography, and the reaction results were calculated.
[0045] According to the above experimental method for catalyzing the semi-hydrogenation of 3-acetylenequinoline, when the catalysts prepared in different embodiments were used for catalytic reaction, the results were as follows:
[0046] 1) Using the catalyst of Example 1, the reaction results are: when the reaction time is 25 min, the conversion rate of 3-acetylene quinoline is 79%, and the selectivity of 3-vinyl quinoline is 99%. When the reaction time is extended to 32 min, the conversion rate of 3-acetylene quinoline is 99%, and the selectivity of 3-vinyl quinoline is 97%. When the reaction time is further extended for 2 h, the selectivity of 3-vinyl quinoline can still maintain 88%.
[0047] 2) Using the catalyst of Example 2, the reaction results are: when the reaction time is 6 min, the conversion rate of 3-ethynylquinoline is 92%, and the selectivity of 3-vinylquinoline is 97%.
[0048] 3) Using the catalyst of Example 3, the reaction results were: when the reaction time was 25 min, the conversion rate of 3-ethynylquinoline was 50%, and the selectivity of 3-vinylquinoline was 98%.
[0049] 4) Using the catalyst of Example 4, the reaction results are: when the reaction time is 25 min, the conversion rate of 3-ethynylquinoline is 76%, and the selectivity of 3-vinylquinoline is 99%.
[0050] 5) Using the catalyst of Example 5, the reaction results are: when the reaction time is 25 min, the conversion rate of 3-ethynylquinoline is 62%, and the selectivity of 3-vinylquinoline is 99%.
[0051] 6) Using the catalyst of Example 6, the reaction results are: when the reaction time is 25 min, the conversion rate of 3-ethynylquinoline is 35%, and the selectivity of 3-vinylquinoline is 99%.
[0052] 7) Using the catalyst of Example 7, the reaction results are: when the reaction time is 25 min, the conversion rate of 3-ethynylquinoline is 48%, and the selectivity of 3-vinylquinoline is 98%.
[0053] 8) Using the catalyst of Example 8, the reaction results are: when the reaction time is 25 min, the conversion rate of 3-ethynylquinoline is 64%, and the selectivity of 3-vinylquinoline is 96%.
[0054] By comparing the above experimental results, it can be seen that oxalylanilide has a more obvious promoting effect on the catalytic performance in the semi-hydrogenation reaction of nitrogen-containing alkynes than other organic ligands. The molar ratio of palladium to oxalylanilide is too little or too much, which shows an inhibitory effect. When the molar ratio of palladium to oxalylanilide is 1:2, its catalytic performance for the semi-hydrogenation of nitrogen-containing alkynes is the best.
[0055] Example 10: Catalytic semi-hydrogenation of 3-acetylenequinoline in a sulfur-containing system using the Pd / C catalyst prepared in Example 1
[0056] 306mg of 3-acetylene quinoline, 10 μ L thiophene, 10mg Pd / C catalyst prepared by embodiment 1 and 5mL of ethanol are added to 50mL stainless steel autoclave, after 3 times of inflating exhaust with hydrogen in the stainless steel autoclave, hydrogen is filled to 0.1MPa and sealed, in 30 ℃ of water bath heating, magnetic stirring, carry out selective hydrogenation reaction, react 25min. After the stopped reaction, the residual hydrogen in the stainless steel autoclave is carefully discharged, and reaction solution is taken out. Adopt centrifugal method that Pd / C catalyst is separated from reaction solution, reaction solution is detected by gas chromatography, and the transformation efficiency that detection and calculation obtain 3-acetylene quinoline is 65%, and the selectivity of 3-vinyl quinoline is 99%.
[0057] Example 11 Catalytic semi-hydrogenation of 3-acetylenequinoline in a sulfur-containing system using the Pd / C catalyst prepared in Example 2
[0058] 306mg of 3-acetylene quinoline, 100 μ L thiophene, 10mg Pd / C catalyst prepared by embodiment 2 and 5mL of ethanol are joined in 50mL stainless steel autoclave, after 3 times of exhaust gas filling with hydrogen in the stainless steel autoclave, fill with hydrogen to 0.1MPa and seal, in 30 ℃ of water bath heating, magnetic stirring, carry out selective hydrogenation reaction, reaction 6min. After the stopped reaction, the residual hydrogen in the stainless steel autoclave is carefully discharged, take out reaction solution. Adopt centrifugal method that Pd / C catalyst is separated from reaction solution, reaction solution gas chromatographic detection, detection and calculation obtain the transformation efficiency of 3-acetylene quinoline and be 78%, the selectivity of 3-vinyl quinoline is 97%.
[0059] By comparing the experimental results of Example 9, Experiment 1, and Examples 10-11, it can be seen that the introduction of oxalylanilide can change the electronic structure of palladium, so that the catalyst has excellent resistance to sulfur poisoning. The strategy of oxalylanilide-modified palladium nanoparticles to resist nitrogen (or sulfur) atom poisoning is universal and has good industrial application prospects.
[0060] Example 12: Semi-hydrogenation of 3-acetylenequinoline using the catalyst used in Example 9 Experiment 1)
[0061] Example 9 Experiment 1) After 2 hours of reaction, the reaction was terminated, the residual hydrogen in the stainless steel autoclave was carefully discharged, and the reaction liquid was taken out. The Pd / C catalyst and the reaction liquid were separated by centrifugation, and the recovered Pd / C catalyst was put into the next batch of reactions. The reaction process was as follows:
[0062] 306 mg of 3-acetylene quinoline, 10 mg of recovered Pd / C catalyst and 5 mL of ethanol were added to a 50 mL stainless steel autoclave. After the stainless steel autoclave was filled and exhausted with hydrogen for 3 times, it was filled with hydrogen to 0.1 MPa and sealed. It was heated in a 30°C water bath and stirred with magnetic force to carry out selective hydrogenation reaction for 25 min. After stopping the reaction, the residual hydrogen in the stainless steel autoclave was carefully discharged and the reaction liquid was taken out. The Pd / C catalyst and the reaction liquid were separated by centrifugation, and the reaction liquid was detected by gas chromatography. The detection and calculation showed that the conversion rate of 3-acetylene quinoline was 75% and the selectivity of 3-vinyl quinoline was 99%.
[0063] By comparing the experimental results of Example 12 and Example 9 Experiment 1), it can be seen that the Pd / C catalyst modified with oxalic acid anilide has good reusability, indicating that it has excellent stability under the reaction conditions.
[0064] Comparative Example 1: Semi-hydrogenation of 3-acetylenequinoline catalyzed by homemade Pd / C catalyst without ligand modification
[0065] Catalyst preparation: 1 ml Pd(NO3 ) 2 The solution (Pd mass concentration is 2 mg / ml) is placed in a 20 ml glass bottle, 12 ml of anhydrous ethanol is added, and after stirring evenly, 200 mg of the homemade porous carbon carrier is added, and the mixture is transferred to an 80°C oil bath and continued to be stirred until the ethanol is completely evaporated. The resulting black powder is reduced at 200°C for 2 h under a hydrogen atmosphere to obtain the catalyst.
[0066] The catalytic reaction of 3-acetylene quinoline semi-hydrogenation was carried out with reference to Example 9, and the catalyst of Comparative Example 1 was used for the reaction. The reaction results were as follows: the conversion rate of 3-acetylene quinoline was 45% and the selectivity of 3-vinyl quinoline was 98% when the reaction time was 25 min. When the reaction time was extended to 45 min, the conversion rate of 3-acetylene quinoline was 99% and the selectivity of 3-vinyl quinoline was 94%. When the reaction time was further extended to 2 h, the selectivity of 3-vinyl quinoline dropped rapidly to 53%.
[0067] The semi-hydrogenation of 3-acetylenequinoline was catalyzed in a sulfur-containing system. The reaction method was as described in Example 10. The catalyst of Comparative Example 1 was used for the reaction. The reaction results were as follows: the conversion rate of 3-acetylenequinoline was 24% after 25 minutes of reaction, and the selectivity of 3-vinylquinoline was 98%.
[0068] Comparative Example 2: Semi-hydrogenation of 3-acetylenequinoline catalyzed by commercial Pd / C catalyst without ligand modification
[0069] Catalytic reaction process: 306 mg of 3-acetylene quinoline, 10 mg of the existing commercial Pd / C catalyst (55% water content) of Comparative Example 2 and 5 mL of ethanol were added to a 50 mL stainless steel autoclave. After the stainless steel autoclave was filled and exhausted with hydrogen 3 times, it was filled with hydrogen to 0.1 MPa and sealed, heated in a 30°C water bath, stirred with magnetic force, and subjected to selective hydrogenation reaction for 180 min. After stopping the reaction, the residual hydrogen in the stainless steel autoclave was carefully discharged and the reaction solution was taken out. The Pd / C catalyst and the reaction solution were separated by centrifugation, and the reaction solution was detected by gas chromatography. The detection and calculation showed that the conversion rate of 3-acetylene quinoline was 53%, and the selectivity of 3-vinyl quinoline was 98%.
[0070] Catalytic reaction process under sulfur-containing conditions: 306 mg of 3-acetylene quinoline, 45 μl of thiophene, 10 mg of the existing commercial Pd / C catalyst (55% water content) of Comparative Example 2 and 5 mL of ethanol were added to a 50 mL stainless steel autoclave. After the stainless steel autoclave was filled and exhausted with hydrogen three times, it was filled with hydrogen to 0.1 MPa and sealed, heated in a 30°C water bath, stirred with magnetic force, and subjected to selective hydrogenation reaction for 180 min. After stopping the reaction, the residual hydrogen in the stainless steel autoclave was carefully discharged and the reaction liquid was taken out. The Pd / C catalyst and the reaction liquid were separated by centrifugation, and the reaction liquid was detected by gas chromatography. The detection and calculation showed that the conversion rate of 3-acetylene quinoline was 8%, and the selectivity of 3-vinyl quinoline was 96%.
[0071] By further comparing the experimental results of Comparative Examples 1-2 and Examples 9-11, it can be concluded that the introduction of oxalylanilide can improve the activity and selectivity of the catalyst in the semi-hydrogenation reaction of nitrogen-containing alkynes, regardless of whether it is homemade Pd / C or commercial Pd / C, and even has good catalytic performance under sulfur-containing conditions. Therefore, this strategy can be applied to industrial scale-up production.
[0072] Comparative Example 3: Semi-hydrogenation of 3-acetylenequinoline catalyzed by Pd / C catalyst supported on conventional activated carbon
[0073] Catalyst preparation: 1 ml Pd(NO 3 ) 2 The solution (Pd mass concentration is 2 mg / ml) is placed in a 20 ml glass bottle, 12 ml of anhydrous ethanol is added, and after stirring evenly, 200 mg of conventional activated carbon (400 mesh, purchased from McLean) is added, and the mixture is transferred to an 80° C. oil bath and continued to be stirred until the ethanol is completely evaporated. The resulting black powder is reduced at 200° C. for 2 h under a hydrogen atmosphere to obtain the catalyst.
[0074] The catalytic reaction of 3-acetylenequinoline semi-hydrogenation was carried out with reference to Example 9, using the catalyst of Comparative Example 3. The reaction results were as follows: after 25 minutes of reaction, the conversion rate of 3-acetylenequinoline was 11%, and the selectivity of 3-vinylquinoline was 94%.
[0075] The semi-hydrogenation of 3-acetylenequinoline was catalyzed in a sulfur-containing system. The reaction method was as described in Example 10. The catalyst of Comparative Example 3 was used for the reaction. The reaction results were as follows: the conversion rate of 3-acetylenequinoline was 4% after 25 minutes of reaction, and the selectivity of 3-vinylquinoline was 98%.
[0076] Comparative Example 4: Semi-hydrogenation of 3-acetylenequinoline catalyzed by Pd / C catalyst modified with oxalylanilide ligand and supported on conventional activated carbon
[0077] Catalyst preparation: 9 mg of oxalylanilide (0.0375 mmol) was placed in a 20 ml glass bottle, 12 ml of anhydrous ethanol was added, stirred evenly, and 1 ml of Pd(NO 3 ) 2 The solution (Pd mass concentration is 2 mg / ml) was stirred at room temperature overnight, and then 200 mg of conventional activated carbon (400 mesh, purchased from McLean) was added, and the mixture was transferred to an 80°C oil bath and continued to be stirred until the ethanol was completely evaporated. The obtained black powder was reduced at 200°C for 2 h under a hydrogen atmosphere to obtain the catalyst.
[0078] The catalytic reaction of 3-acetylenequinoline semi-hydrogenation was carried out with reference to Example 9, using the catalyst of Comparative Example 4. The reaction results were as follows: after 25 minutes of reaction, the conversion rate of 3-acetylenequinoline was 38%, and the selectivity of 3-vinylquinoline was 97%.
[0079] The semi-hydrogenation of 3-acetylenequinoline was catalyzed in a sulfur-containing system. The reaction method was as described in Example 10. The catalyst of Comparative Example 4 was used for the reaction. The reaction results were as follows: the conversion rate of 3-acetylenequinoline was 29% after 25 minutes of reaction, and the selectivity of 3-vinylquinoline was 98%.
[0080] It can be seen from the experimental results of Comparative Examples 3-4 that similar conclusions can be obtained by using conventional activated carbon as a carrier and preparing the catalyst using the same ligand modification method, but the reaction effect is worse than that of the homemade porous carbon carrier in the embodiment of the present invention.
[0081] The contents described in this specification are merely an enumeration of implementation forms of the inventive concept, and the protection scope of the present invention should not be regarded as being limited to the specific forms described in the embodiments.
Claims
1. A ligand-modified Pd / C catalyst, characterized in that The catalyst comprises a porous carbon carrier, palladium nanoparticles loaded on the carrier and an organic ligand coordinated on the catalyst surface, wherein the mass of the palladium nanoparticles is 0.5-2% of the mass of the porous carbon carrier, the organic ligand is selected from at least one of oxalic acid anilide, L-lysine, ethylenediaminetetraacetic acid or oleylamine, and the molar ratio of the organic ligand to palladium is 1-8:
1.
2. A ligand-modified Pd / C catalyst as claimed in claim 1, characterized in that The mass of the palladium nanoparticles is 0.8-1.2% of the mass of the porous carbon support, the organic ligand is selected from oxalic acid anilide, and the molar ratio of the organic ligand to palladium is 2-3:
1.
3. A ligand-modified Pd / C catalyst as claimed in claim 1, characterized in that The preparation method of the porous carbon carrier comprises the following steps: cellulose and ammonium bicarbonate are uniformly mixed in a mortar at a mass ratio of 1:0.8-1.2, then calcined at 700-900°C for 1-3h under an Ar atmosphere, cooled to room temperature, and the obtained black powder is washed and dried overnight to obtain the porous carbon.
4. The method for preparing a ligand-modified Pd / C catalyst according to claim 1, characterized in that The method comprises the following steps: adding an organic ligand to anhydrous ethanol, stirring evenly, then adding a palladium precursor solution, stirring at room temperature overnight, then adding a porous carbon carrier, wherein the concentration of the porous carbon carrier dispersed in the anhydrous ethanol is 5-30 g / L, transferring the mixed solution to a 70-90° C. oil bath heating environment and continuing to stir until the ethanol is completely evaporated, and reducing the obtained black powder at 180-250° C. for 1-3 hours in a hydrogen atmosphere to obtain the catalyst.
5. The method for preparing a ligand-modified Pd / C catalyst according to claim 4, characterized in that The palladium precursor is Pd(NO3)2, PdCl2 or K2PdCl4, preferably Pd(NO3)2; the mass of the Pd element in the palladium precursor is 0.5-2% of the mass of the porous carbon support, preferably 0.8-1.2%.
6. The method for preparing a ligand-modified Pd / C catalyst according to claim 4, characterized in that The organic ligand is selected from at least one of oxalylanilide, L-lysine, ethylenediaminetetraacetic acid or oleylamine, preferably oxalylanilide, and the molar ratio of the organic ligand to palladium is 1-8:1, preferably 2-3:
1.
7. Use of a ligand-modified Pd / C catalyst as claimed in claim 1 in catalyzing the selective hydrogenation reaction of nitrogen-containing alkynes.
8. The use according to claim 7, characterized in that The nitrogen-containing alkyne is mixed with a solvent, and then the reaction liquid is selectively hydrogenated under the action of a Pd / C catalyst in a hydrogen atmosphere to generate a nitrogen-containing olefin; wherein the hydrogenation reaction temperature is 0 to 100° C., and the reaction hydrogen pressure is 0.1 to 4 MPa; and the solvent is water, ethanol, dichloromethane, tetrahydrofuran or n-hexane.
9. The use according to claim 8, characterized in that The mass of the catalyst is 1-10%, preferably 2-5%, of the mass of the nitrogen-containing alkyne; the temperature for the selective hydrogenation reaction is 25-40° C.; the hydrogen pressure of the reaction is 0.1-0.5 MPa; and the solvent is ethanol.
Citation Information
Patent Citations
Oxanilide derivative synthesis method
CN106242989A
Preparation method and application of miscanthus mesoporous activated carbon-based palladium nanoparticle catalyst
CN111068667A
Absorbents and process for producing the same, absorbable constructs and absorbable articles
SG94638A1